Elmo's world. Happy holidays! [videorecording (DVD)] - Diego, Ken; Parente, Carol-Lynn, 1963-; Ferraro, Christine; Clash, Kevin; Clash, Kevin; Ripa, Kelly; Hall, Charles Edward; Leitão, Júlio T.; Irwin, Bill, 1950-; Jeter, Michael, 1952-2003; Chenoweth, Kristin (Sesame Workshop, 2009)
Elmo is gearing up to celebrate Christmas. But what present will he give Dorothy, his beloved goldfish? As he searches for an answer, he learns about holidays around the world.